CGAS-STING effectively restricts murine norovirus infection but antagonizes the antiviral action of N-terminus of RIG-I in mouse macrophages. (1st January 2021) - Yu, Peifa; Miao, Zhijiang; Li, Yang; Bansal, Ruchi; Peppelenbosch, Maikel P.; Pan, Qiuwei
ABSTRACT: Although cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling has been well recognized in defending DNA viruses, the role of cGAS-STING signaling in regulating infection of RNA viruses remains largely elusive. Noroviruses, as single-stranded RNA viruses, are the main causative agents of acute viral gastroenteritis worldwide. This study comprehensively investigated the role of cGAS-STING in response to murine norovirus (MNV) infection. We found that STING agonists potently inhibited MNV replication in mouse macrophages partially requiring the JAK/STAT pathway that induced transcription of interferon (IFN)-stimulated genes (ISGs). Loss- and gain-function assays revealed that both cGAS and STING were necessary for host defense against MNV propagation. Knocking out cGAS or STING in mouse macrophages led to defects in induction of antiviral ISGs upon MNV infection. Overexpression of cGAS and STING moderately increased ISG transcription but potently inhibited MNV replication in human HEK293T cells ectopically expressing the viral receptor CD300lf. This inhibitory effect was not affected by JAK inhibitor treatment or expression of different MNV viral proteins. Interestingly, STING but not cGAS interacted with mouse RIG-I, and attenuated its N-terminus-mediated anti-MNV effects. Our results implicate an essential role for mouse cGAS and STING in regulating innate immune response and defending MNV infection. This further strengthens the evidence of cGAS-STING signaling in response to RNA virus infection.